2019
DOI: 10.16984/saufenbilder.445146
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antibiofilm activity of green synthesized silver nanoparticles by using aqueous leaf extract of Thymus serpyllum

Abstract: Recently, metal nanoparticles have attracted the attention of researchers due to their unique properties when compared with bulk materials and have become used in many fields of application. In this study, green synthesis of Ag nanoparticles (AgNPs) was investigated by using the aqueous extract of T. serpyllum leaves. In addition, antimicrobial and antibiofilm activities of the synthesized AgNPs were evaluated in this study. Further, ultravioletvisible spectroscopy (UV-Vis), fouirer transform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…It also induced the formation of bactericidal reactive oxygen species (ROS) which permanently deactivated bacterial respiratory chain lactate dehydrogenase (LDH) [48]. At the same time, the inhibition effect of nanoparticles on S. aureus was more than E. coli in general, and these results were in line with the studies in the literature [49,50]. This study suggested that nano-silver can be a competent antibacterial agent against various pathogenic microbes.…”
Section: Analysis Of Antibacterial Activities Of Biosynthesized Silvesupporting
confidence: 72%
“…It also induced the formation of bactericidal reactive oxygen species (ROS) which permanently deactivated bacterial respiratory chain lactate dehydrogenase (LDH) [48]. At the same time, the inhibition effect of nanoparticles on S. aureus was more than E. coli in general, and these results were in line with the studies in the literature [49,50]. This study suggested that nano-silver can be a competent antibacterial agent against various pathogenic microbes.…”
Section: Analysis Of Antibacterial Activities Of Biosynthesized Silvesupporting
confidence: 72%
“…Interestingly, Eric and Torlak synthesized Ag nanoparticles (AgNPs) by using the aqueous leaf extract of Thymus serpyllum. The antibiofilm data revealed that AgNPs (100 μg/ml) inhibited the biofilm formation by 73% in S. aureus (Erci and Torlak, 2019).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Our findings suggest that Gel-AgNPs can serve as a potential antibacterial agent against Grampositive and Gram-negative bacteria. Silver nanoparticles cause structural and morphological variations in bacterial cells, leading to cell death (Erci and Torlak, 2019). Recent research has shown that using essential oils and silver nanoparticles together produces a synergistic effect in antimicrobial activity.…”
Section: Antibacterial Activities Of Synthesized Silver Nanoparticles...mentioning
confidence: 99%
“…Green synthesis has attracted considerable interest in materials science as a reliable, sustainable, and environmentally friendly protocol for the synthesis of a variety of nanomaterials, such as metal/metal oxide nanomaterials (Erci and Cakir-Koc, 2021;Erci et al, 2020Erci et al, , 2018Erci and Torlak, 2019). Therefore, green synthesis is recognized as an important tool that is extensively used in laboratories and industry to lessen the harmful effects associated with traditional nanoparticle synthesis methods (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%